Pengaruh Spesialisasi Industri Auditor, Reputasi Auditor, dan Audit Tenure terhadap Audit Report Lag - Dyah Puspa Arumningtyas; Adi Firman Ramadhan (Journal of Economics and Business, 2019)
This study aims to empirically examine the relationship between industry auditor specialization, auditor reputation, and audit tenure, to audit report lag in manufacturing companies listed on the Indonesia Stock Exchange in 2015-2017. The population in this study are manufacturing companies listed on the Indonesia Stock Exchange in 2015-2017. The research sample consisted of 67 companies listed on the Indonesia Stock Exchange for the period 2015-2017. The data used in this study are secondary data and sample selection using purposive sampling method. The analysis model uses multiple linear regression analysis. The results of this study indicate that auditor industry specialization has a negative effect on audit report lag, auditor reputation has no effect on audit report lag, and audit tenure has a negative effect on audit report lag.